A photographer among greenery, that is about portraying nature - Kania, Marcin (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
The topic of the article is nature photography. This type of human creative activity is currently very popular among artists and audiences. The article discusses several important issues related to the creation of the image of nature. Photographing nature can be enjoyed by both — beginners and professional photographers.